ESTIMATION OF GENETIC DIVERSITY IN MAIZE INBRED LINES FOR KEY AGRO-PHONOLOGICAL AND MORPHOLOGICAL TRAITS - KAMAL , N; SHOUKAT, F; SULTAN , R; SALEEM , S; KHANUM , S; REHMAN, ZU; SALEEM , S; AHMED , MF; SAJID , MN; AKHTAR, N; et al. (Biological and Clinical Sciences Research Journal, 2024)
Assessment of genetic diversity in cultivated as well as wild germplasm is the prerequisite for improving any crop through breeding and hybridization. The current experimental study was conducted at Maize Research Sub-Station, Charra Pani, Murree, Punjab, Pakistan during the crop season 2023-24 to evaluate the elite maize inbred lines for their genetic variation for key agro-phonological and grain yield associated traits including days to tessling, days to silking, plant height, cob height, cob length, number of grains per row, number of rows per cob, cob girth and grain yield. The experiment was laid out under randomized complete block design with two replications where row-to-row distance was maintained at 75 cm and plant-to-plant distance was maintained at 20 cm. The data was collected for the above given traits which were then subjected to statistical analysis. The results from the analysis of variance revealed that significant genetic variability was present among study key plant traits in maize inbred lines. Furthermore, correlation coefficient analysis was carried out to compute the magnitude and direction of association between different plant traits within and with grain yield. The results unveiled that grain yield had a positive and significant correlation with plant height (r = 0.4966*), number of grains per row (r = 0.5615*) and cob girth (r = 0.5386*) in studied maize inbred lines. To evaluate the variability present among maize inbred lines, principal component analysis (PCA) along with PC1/PC2 biplot was used which categorized these twenty-eight maize inbred lines into nine principal components (PCs). As revealed in PCA, plant height, cob height, cob length, number of grains per row, cob girth and grain yield were the major contributing traits to genetic variability present in the data along with twelve maize inbred lines i.e., YBH-1-1, YBH-1-2, YBH-1-5, YBH-1-6, YBH-1-8, YBH-1-9, YBH-1-10, YBH-2-11, YBH-2-16, YBH-2-17, YBH-3-27 and YBH-3-28.